Joining characteristics of oxidized SiC particles reinforced Al-Mg matrix composite prepared by reaction infiltration processing - Shi, ZL; Ochiai, S; Hojo, M; Lee, J; Gu, MY; Lee, H (MATERIALS RESEARCH SOCIETY, 2001)
The joining characteristics of oxidized SIC particles with Al-Mg alloy during reaction infiltration processing for fabrication of the composite were studied. From the measurement of weight changes due to the transformation from SiC into SiO2, it became clear that the thickness of SiO2 layer which was formed at the surface of SiC particles increased parabolically with holding time at the given exposing temperatures. The degree of oxidation of the preform made by SiC particles can be controlled by the application of the present oxidation data. The microstructure observed by field emission scanning electron microscopy showed network skeleton via necklike oxidized-joining among the SIC particles and the compressive strength of the perform increased with oxidation temperature, Furthermore, the microstructure of the composite which was fabricated by Al-2 wt% Mg alloy via reaction infiltration processing was examined and the formation of spinel was observed to join the matrix with the particles like a bridge, which is suitable to make the complicate and strong preforms for the near net-shape composites application in electronic packaging.
Keywords: SILICON-CARBIDE; OXIDATION; OXIDE